In Dissent of Dialogue: Why Dialogue is a Dangerous Metaphor for Conceptualising - Nathan, Hannah (Victoria University of Wellington Law Review, 2025)
The senior courts of Aotearoa may formally declare an Act as inconsistent with the New Zealand Bill of Rights Act 1990, a remedy which now requires an executive response and debate on the matter. Given this cross-parliamentary involvement and the constitutional centrality of human rights, the precise relationship between the courts and Parliament under the Bill of Rights Act has attracted great attention. Internationally, these relationships have been metaphorically compared to a dialogue, framing a declaration as the judiciary "speaking" to Parliament and Parliament "speaking back" to facilitate robust, collaborative engagement with human rights protection. Dialogue has infiltrated the development of Aotearoa’s declaration of inconsistency (DOI) framework, albeit inconsistently, resulting in a multi-branch remedial framework which is conceptually confused. Despite the legislature’s approval of dialogue, it was rejected by the Supreme Court. This puts the key actors in DOIs at odds as to the remedy’s purpose and underlying constitutional relationships. This article argues that DOIs conceived as dialogue masks reality. Dialogue has been inappropriately imported into this remedy, and as this article argues, should be reconceptualised to better reflect the reality of practice in Aotearoa, as well as to abate the inherent dangers of the metaphor. By tracing the judicial development and subsequent legislative affirmation of DOIs, this article traces dialogue’s implementation in the conception of the DOI to demonstrate that its current form is unworkable. A case study of Make It 16 reveals how these failures unfold and highlights the dangers of dialogue in Aotearoa. Finally, this article attempts to address these dangers by recasting the metaphor as Discourse, which better reflects Aotearoa’s constitutional landscape and promotes richer parliamentary responses to declarations.